The Implementation of the Khalifah fil Ard Concept in Islamic Religious Education for Strengthening Environmental Care Character: A Study in Jambi Province - Doni Pratama; Baili Baili; Joni Juli Yandra; Andryadi Andryadi; Mabruri Mabruri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The degradation of peatland ecosystems, pollution of the Batanghari River, and the increasing risk of forest and land fires in Jambi Province demand educational responses that are not only technocratic but also grounded in spiritual and axiological values. The Qur’anic concept of Khalifah fil Ard offers a relevant theological and ethical framework for fostering students’ environmental responsibility. This study analyzes the implementation of this concept in Islamic Religious Education (IRE) and its impact on strengthening students’ environmental responsibility in educational institutions across Jambi Province. The research employed a sequential explanatory mixed-methods design involving 248 junior secondary school students (SMP/MTs) and eight Islamic Religious Education teachers from Jambi City and Muaro Jambi Regency. Quantitative data were collected using an expert-validated Environmental Responsibility Character Scale (α = 0.87), while qualitative data were obtained through in-depth interviews, participant observation, and analysis of instructional documents. The results of the paired-sample t-test revealed a significant improvement in students’ environmental responsibility scores (t(247) = 14.32, p < 0.001, d = 1.92). Qualitative findings identified a four-phase implementation model consisting of: (1) tadabbur alam (contemplation of nature), (2) theological reflection, (3) practical environmental action based on Jambi Malay local wisdom, and (4) collaborative evaluation. Supporting factors included the implementation of the Merdeka Curriculum, teachers’ pedagogical competence, and strong school–community partnerships. Major challenges involved limited instructional time, the scarcity of contextual ecological teaching materials, and unequal access to digital infrastructure in peripheral areas. The study concludes that the concept of Khalifah fil Ard is effective as an axiological framework for Islamic Religious Education when integrated with reflective pedagogy and local environmental problem-based projects. The study recommends the development of Jambi-contextualized teaching modules, professional training for Islamic Religious Education teachers in Islamic ecopedagogy, and cross-sector collaboration involving educational authorities and religious institutions to strengthen value-based environmental education.